Preparation method of nano composite material containing manganese-zirconium-based MOFs confinement zero-valent iron and construction method for constructing electrochemical sensor by using nano composite material

By using nanocomposite materials containing manganese zirconium-based MOFs limited-domain zero-valent iron in electrochemical sensors, the problems of low sensitivity and poor stability of mercury ion detection in electrochemical detection methods are solved, and efficient detection of trace mercury and Improvement of electrocatalytic performance.

CN119187584APending Publication Date: 2024-12-27HEFEI UNIV OF TECH
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202410958592.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-07-17
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

The existing electrochemical detection methods have low sensitivity and poor stability for mercury ions (Hg2+), and nano zero-valent iron materials have problems of agglomeration and easy oxidation, which limits their large-scale application in electrochemical detection.

Method used

Using a nanocomposite material containing manganese zirconium-based MOFs limited-domain zero-valent iron, Fe ions are immersed in MOF nanopores by a dual solvent method, and Fe@PCN-222(Mn) composite material is prepared as a modified material for electrochemical sensors. MOF nanopore confined nano zero-valent iron improves its electrocatalytic performance and stability.

Benefits of technology

It significantly improves the detection sensitivity and stability of electrochemical sensors to Hg2+, improves the agglomeration and easy oxidation problems of nano zero-valent iron, enhances electrocatalytic performance, and achieves efficient detection of trace mercury.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119187584A_ABST
    Figure CN119187584A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of electrochemical analysis and detection, in particular to a preparation method of a nano composite material containing manganese-zirconium-based MOFs confinement zero-valent iron and a construction method for constructing an electrochemical sensor by using the nano composite material. A preparation method of a nano composite material containing manganese-zirconium-based MOFs confinement zero-valent iron comprises the following steps: dissolving a PCN-222 (Mn) precursor in DMF for ultrasonic treatment, stirring and heating a suspension I after ultrasonic treatment, adding Fe (NO3) 2 and p-aminobenzoic acid, continuously stirring, filtering and drying, then transferring into ethylene glycol, dropwise adding NaBH4 for reaction, filtering, washing, and drying to obtain the nano composite material containing manganese-zirconium-based MOFs confinement zero-valent iron. A third suspension is obtained. And centrifuging the suspension III to obtain a solid II, washing the solid II with an acetone solution, and drying. The prepared manganese-zirconium-based MOFs confinement zero-valent iron nano material can be used for modifying an electrode and constructing an electrochemical sensor, and the constructed electrochemical sensor can effectively detect trace Hg < 2 + > in a water environment, and has high sensitivity and good stability on Hg < 2 + > electrochemical detection.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of electrochemical analysis and detection, and specifically to a method for preparing a nanocomposite material containing manganese-zirconium-based MOFs confined zero-valent iron and a method for constructing an electrochemical sensor using the nanocomposite material. Background Art

[0002] Mercury is one of the most toxic heavy metals in the world and is mainly found in water environments in the form of mercury ions (Hg 2+ ) exists in the form of Hg 2+ Mercury ions are easily enriched in aquatic organisms and enter the human body through the food chain. Even trace amounts of mercury ions can have varying degrees of impact on the ecological environment and human health. Therefore, it is urgent to develop simple, fast, and efficient on-site mercury ion analysis methods. So far, there are many methods for analyzing mercury ions, which are mainly divided into colorimetry, fluorescence, surface enhanced Raman scattering, surface plasmon resonance, etc. according to the detection characteristics. These methods often have certain limitations, such as complex operation, cumbersome pre-treatment links, and high costs.

[0003] Electrochemical detection methods stand out among many detection methods for their high sensitivity, good stability, low cost and ability to achieve in-situ detection. 0 ) has the reactivity of nanomaterials and the reduction characteristics of zero-valent iron, which is beneficial to the adsorption and reduction of heavy metal ions in the electrochemical analysis process, thereby amplifying the electrochemical response signal of pollutants. Therefore, it can be used as a material for modifying electrodes in the field of electrochemical analysis. However, existing zero-valent iron nanomaterials have problems such as agglomeration and easy oxidation, which limits their large-scale production and application in electrochemical detection methods. And the electrochemical detection methods in the prior art are limited in the detection of Hg 2+ When conducting detection, it has the characteristics of low detection sensitivity and poor stability. Summary of the invention

[0004] In order to solve the problem of electrochemical detection method for Hg 2+ In order to solve the problems of low detection sensitivity and poor stability during detection, the present invention provides a method for preparing a nanocomposite material containing manganese-zirconium-based MOFs confined zero-valent iron.

[0005] To achieve the above objectives, the technical solution adopted by the present invention is: a method for preparing a nanocomposite material containing manganese-zirconium-based MOFs confined zero-valent iron, which comprises the following steps:

[0006] The PCN-222(Mn) precursor was dissolved in DMF and subjected to ultrasound to obtain a suspension 1;

[0007] The suspension was placed on a stirrer and heated to 90°C. Fe(NO3 ) 2 and p-aminobenzoic acid, and continue stirring for a while to obtain suspension 2;

[0008] The suspension 2 is filtered to obtain a solid 1, and the solid 1 is dried; the dried solid 1 is transferred into ethylene glycol, and NaBH is added dropwise into the ethylene glycol. 4 , allowing it to react for a period of time to obtain suspension three;

[0009] The suspension three is centrifuged to obtain a solid two, the collected solid two is washed with an acetone solution for multiple times, and the washed solid two is dried to obtain a manganese-zirconium-based MOFs-confined zero-valent iron nanomaterial, the prepared manganese-zirconium-based MOFs-confined zero-valent iron nanocomposite material contains MOF nanopores, and can confine nano-zero-valent iron in the manganese-zirconium-based MOF nanopores; the manganese-zirconium-based MOFs-confined zero-valent iron nanocomposite material is used as an electrode modification material to modify and detect Hg 2+ Electrodes in electrochemical sensors.

[0010] As a further improvement of the above scheme, the preparation method of the PCN-222 (Mn) precursor comprises the following steps:

[0011] ZrOCl 2 8H 2 O, Mn-TCPP and benzoic acid were dissolved in DMF to obtain suspension 4;

[0012] The suspension 4 is placed in a reaction kettle with a polytetrafluoroethylene liner, and the reaction is continued at 120° C. for 24 hours to obtain a suspension 5;

[0013] The suspension is cooled and filtered to obtain crystals, which are PCN-222 (Mn) crystals. The PCN-222 (Mn) crystals after filtration are collected, and then the collected PCN-222 (Mn) crystals are washed with DMF and ethanol for multiple times, respectively. Finally, the washed crystals are placed at 120° C. and vacuum dried for a period of time to obtain a PCN-222 (Mn) precursor.

[0014] As a further improvement of the above scheme, the preparation method of Mn-TCPP comprises the following steps:

[0015] TCPP and MnCl 2 ·4H 2 O were added to DMF and dissolved by ultrasonic to obtain a mixed solution 1, the mixed solution 1 was refluxed at 140°C for 12h, and then cooled to room temperature, washed with DMF and ethanol and dried to obtain a solid 3;

[0016] The fixed three is redispersed in a mixture of THF and MeOH to obtain a mixture of two, and then 0.6 mol / L KOH with a volume of 100 mL is added to the mixture of two, and refluxed at 80° C. for 12 h, and then 1 mol / L HCl is added dropwise to the refluxed mixture of two, and solid four will precipitate in the mixture of two, and 1 mol / L HCl is added continuously until the solid four is no longer precipitated;

[0017] The solid four in the mixed solution two is collected by filtering the mixed solution two, and the collected solid four is washed with deionized water and vacuum dried to obtain the Mn-TCPP.

[0018] As a further improvement of the above scheme, the nanocomposite material containing manganese-zirconium-based MOFs confined zero-valent iron is prepared by a double solvent method.

[0019] As a further improvement of the above scheme, the prepared manganese-zirconium-based MOFs-confined zero-valent iron nanocomposite material has MOF nanopores, and the MOF nanopores are used to confine nano-zero-valent iron in the MOF nanopores to fix the nano-zero-valent iron.

[0020] As a further improvement of the above scheme, the prepared manganese-zirconium-based MOFs-confined zero-valent iron nanocomposite material contains Mn-N 4 structure, the Mn-N 4 The structure acts as an active site for redox reactions to improve the catalytic activity of redox reactions.

[0021] A method for constructing an electrochemical sensor using a nanocomposite material containing manganese-zirconium-based MOFs confined zero-valent iron, which includes preparing the nanocomposite material containing manganese-zirconium-based MOFs confined zero-valent iron to obtain a nanocomposite material containing manganese-zirconium-based MOFs confined zero-valent iron, and the nanocomposite material containing manganese-zirconium-based MOFs confined zero-valent iron is used as a modified electrode material to modify an electrode in an electrochemical sensor.

[0022] As a further improvement of the above scheme, the method for constructing an electrochemical sensor using the nanocomposite material containing manganese-zirconium-based MOFs confined zero-valent iron includes modifying an electrode using the prepared nanocomposite material containing manganese-zirconium-based MOFs confined zero-valent iron, and the specific steps of modifying the electrode are: dissolving the prepared nanocomposite material containing manganese-zirconium-based MOFs confined zero-valent iron in deionized water and dispersing it evenly by ultrasound to obtain a suspension six; aspirating the suspension six with a micropipette and dropping it into the electrode of the electrochemical sensor to obtain a modified electrode; and leaving the modified electrode in the air to dry.

[0023] As a further improvement of the above scheme, the electrode needs to be pretreated before being modified with a nanocomposite material containing manganese-zirconium-based MOF confined zero-valent iron, and the pretreatment steps are: polishing the electrode with 1.0μm, 0.3μm and 0.05μm alumina powders respectively until the electrode presents a mirror surface; then, the polished electrode is placed in a nitric acid aqueous solution, an ethanol aqueous solution and deionized water for ultrasonication respectively, and the electrode after ultrasonication is dried at room temperature for use.

[0024] As a further improvement of the above scheme, the electrochemical sensor constructed is used to detect trace Hg in water environment. 2+ The electrochemical sensor detects Hg 2+ The concentration range is 0.1μmol / L~1μmol / L.

[0025] Compared with the prior art, the present invention has the following beneficial effects:

[0026] (1) The present invention uses a dual solvent method to infiltrate Fe ions into MOF nanopores to synthesize a manganese-zirconium-based MOFs-confined zero-valent iron nanocomposite, namely Fe@PCN-222(Mn), and uses it as an electrochemical modification material to modify electrodes and construct an electrochemical sensor, thereby using the constructed electrochemical sensor to detect trace mercury in water environments, which can effectively improve the constructed electrochemical sensor's sensitivity to Hg 2+ The sensitivity of electrochemical detection and the stability during detection.

[0027] (2) The nanocomposite material containing manganese-zirconium-based MOFs confined zero-valent iron prepared by the present invention can utilize MOF nanopores to confine nano-zero-valent iron to improve the problems of nano-zero-valent iron agglomeration and easy oxidation, thereby improving the electrocatalytic performance of the prepared nanocomposite material containing manganese-zirconium-based MOFs confined zero-valent iron.

[0028] (3) The manganese-zirconium-based MOFs-confined zero-valent iron nanocomposite prepared by the present invention has a MOF multi-level pore structure. The MOF multi-level pore structure can significantly promote the high diffusion transfer and reaction of substrates or intermediates during the electrochemical reaction, thereby improving the detection sensitivity of the constructed electrochemical sensor.

[0029] (4) The manganese-zirconium-based MOFs-confined zero-valent iron nanocomposite prepared by the present invention contains iron and manganese, and the synergistic catalytic effect of the iron-manganese bimetallic active center enables the electrochemical sensor constructed by modifying the electrode with the nanocomposite to detect Hg 2+ It can show excellent detection performance and good stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1XRD patterns of PCN-222, PCN-222(Mn), Fe / PCN-222(Mn) and Fe@PCN-222(Mn) in the present invention.

[0031] Figure 2 SEM images of the morphology of Fe / PCN-222(Mn) and Fe@PCN-222(Mn) in the present invention.

[0032] Figure 3 TEM images of the morphology of Fe / PCN-222(Mn) and Fe@PCN-222(Mn) in the present invention.

[0033] Figure 4 is the structural formula of Mn-TCPP prepared in the present invention.

[0034] Figure 5 The electrochemical sensors constructed by modifying electrodes with PCN-222, PCN-222(Mn), Fe / PCN-222(Mn) and Fe@PCN-222(Mn) prepared in the present invention for 0.7 μM Hg 2+ The electrochemical response signal curve obtained by detection.

[0035] Figure 6 The electrochemical sensor of the Fe / PCN-222 (Mn) modified electrode was used to test the above Hg concentrations. 2+ Graph of different voltages and response currents.

[0036] Figure 7 The electrochemical sensor of the Fe / PCN-222 (Mn) modified electrode in the present invention tests Hg at different concentrations 2+ The standard curve of

[0037] Figure 8 The electrochemical sensor of the Fe@PCN-222 (Mn) modified electrode in the present invention tests the Hg in the above different concentration ranges. 2+ Graph of different voltages and response currents.

[0038] Fig. 9 The electrochemical sensor of the Fe@PCN-222(Mn) modified electrode was used to test Hg at different concentrations. 2+ The standard curve of

[0039] Fig.10 Electrochemical sensor constructed by Fe@PCN-222(Mn) modified electrode for Hg adsorption 2+ XPS total spectra before and after.

[0040] Fig.11 for Fig.10 Enlarged view of (a).

[0041] Fig.12 for Fig.10 Enlarged view of (b).

[0042] Fig.13 for Fig.10 Enlarged view of (c).

[0043] Fig.14 for Fig.10 Enlarged view of (d).

[0044] Fig.15 for Fig.10 Enlarged view of (e).

[0045] Fig.16 for Fig.10 Enlarged view of (f). DETAILED DESCRIPTION

[0046] The present invention is further described below in conjunction with specific implementation methods. It should be noted that, under the premise of no conflict, the various embodiments or technical features described below can be arbitrarily combined to form a new embodiment.

[0047] In the description of the present invention, it should be noted that for directional words, such as the terms "center", "lateral", "longitudinal", "length", "width", "thickness", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside", "outside", "clockwise", "counterclockwise" and the like indicating directions and positional relationships are based on the directions or positional relationships shown in the drawings, which are only for the convenience of describing the present invention and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific direction, be constructed and operated in a specific direction, and cannot be understood as limiting the specific protection scope of the present invention. The terms "first", "second", etc. in the specification and claims of the present invention are used to distinguish similar objects, and are not necessarily used to describe a specific order or sequence. The terms "including" and "having" in the specification and claims of the present invention and any variations thereof are intended to cover non-exclusive inclusions, for example, a process, method, system, product or device including a series of steps or units is not necessarily limited to those steps or units clearly listed, but may include other steps or units that are not clearly listed or inherent to these processes, methods, products or devices.

[0048] Example 1

[0049] The present embodiment provides a method for preparing a nanocomposite material containing manganese-zirconium-based MOFs confined zero-valent iron, comprising the following steps:

[0050] (1) dissolving the PCN-222(Mn) precursor in DMF and performing ultrasound to make it uniformly dispersed to obtain a suspension 1;

[0051] (2) The suspension was heated to 90°C on a stirrer and Fe(NO 3 ) 2 and p-aminobenzoic acid, and continue stirring for a while to obtain suspension 2;

[0052] (3) Filter the suspension 2 to obtain a solid 1, and dry the solid 1; transfer the dried solid 1 into ethylene glycol, and add NaBH dropwise into the ethylene glycol. 4 , allowing it to react for a period of time to obtain suspension three;

[0053] (4) The suspension three is centrifuged to obtain a solid two, the collected solid two is washed with an acetone solution for multiple times, and the washed solid two is dried to obtain a nanocomposite material containing manganese-zirconium-based MOFs confined zero-valent iron.

[0054] Wherein, the preparation method of the PCN-222(Mn) precursor in step (1) comprises the following steps:

[0055] (11) ZrOCl 2 8H 2 O, Mn-TCPP and benzoic acid were dissolved in DMF to obtain suspension 4;

[0056] (12) placing the suspension 4 in a reaction kettle lined with polytetrafluoroethylene, and reacting at 120° C. for 24 h to obtain a suspension 5;

[0057] (13) After cooling the suspension, the suspension is filtered to obtain crystals, which are PCN-222(Mn) crystals. The PCN-222(Mn) crystals after filtration are collected, and then the collected PCN-222(Mn) crystals are washed multiple times with DMF and ethanol respectively. Finally, the washed crystals are placed at 120° C. and vacuum dried for a period of time to obtain a PCN-222(Mn) precursor.

[0058] Wherein, the preparation method of Mn-TCPP in step (11) comprises the following steps:

[0059] (111) TCPP and MnCl 2 ·4H 2 O were added to DMF and dissolved by ultrasonic to obtain a mixed solution 1, the mixed solution 1 was refluxed at 140°C for 12h, and then cooled to room temperature, washed with DMF and ethanol and dried to obtain a solid 3;

[0060] (112) Solid 3 is redispersed in a mixture of THF and MeOH to obtain a mixture 2, and then 0.6 mol / L KOH in a volume of 100 mL is added to the mixture 2, and the mixture is refluxed at 80 °C for 12 h. Then, 1 mol / L HCl is added dropwise to the refluxed mixture 2, and solid 4 is precipitated in the mixture 2. 1 mol / L HCl is added continuously until solid 4 is no longer precipitated.

[0061] (113) The solid phase 4 in the mixed solution 2 is collected by filtering the mixed solution 2, and the collected solid phase 4 is washed with water and dried in a vacuum to obtain Mn-TCPP.

[0062] In the present invention, metal organic framework compounds (i.e. MOFs) have the characteristics of large specific surface area, high porosity, orderly and flexible structure, easy functionalization, etc., and are widely used in pollutant treatment. MOFs have tunable coordination space in the cavity and on the surface, which makes them a promising new catalyst carrier, which can be used to carry nano ions. Among them, MOFs synthesized by organic functional ligands of metal-porphyrin structure have excellent catalytic activity and biochemical stability. However, selecting suitable porphyrin has a crucial influence on the regulation of MOFs pore structure and morphology size, wherein the porous coordination network (PCN) synthesized by using meso-tetra (4-carboxylphenyl) porphine as organic ligand is widely used in the adsorption catalysis field of pollutants. Therefore, in the present embodiment, TCPP (meso-tetra (4-carboxylphenyl) porphine) is used as organic functional ligand.

[0063] As a typical porphyrin-based MOF, PCN-222 has a 3D topological structure and large pores that are conducive to the rapid diffusion of substrate molecules. In this embodiment, by selecting PCN-222, its 3D topological structure and large pores can facilitate the rapid diffusion of nano-zero-valent iron, thereby effectively solving the problem of agglomeration of nano-zero-valent iron in the prior art. In addition, anchoring different types of active substances in the cavity of PCN-222 can adjust the charge density distribution and further improve the stability and electrocatalytic activity of the material.

[0064] At the same time, porphyrin-based Zr-MOFs have excellent chemical stability under harsh conditions. The changes in 4-connectivity and symmetry provide many topological structural possibilities, which can be combined with the same TCPP and Zr 6 The nodes form different frameworks and thus have different chemical stabilities. 2 8H 2The solvothermal reaction of O and TCPP in DMF resulted in the strong Zr-O bond in PCN-222, which makes it exhibit excellent chemical and thermal stability, so that the prepared nanocomposite material containing manganese zirconium-based MOFs confined zero-valent iron has good stability. Therefore, the nanocomposite material containing manganese zirconium-based MOFs confined zero-valent iron is used as a modified electrode material to modify the electrode of the electrochemical sensor, which can effectively improve the stability of the constructed electrochemical sensor.

[0065] Based on this, the present invention fixes the nano zero-valent iron by fixing the nano zero-valent iron on the surface of the carrier or capturing it in the pores, thereby improving the performance of the nano zero-valent iron.

[0066] The raw materials for preparing the nanocomposite material containing manganese zirconium-based MOFs confined zero-valent iron in the present invention include PCN-222 and ZrOCl 2 8H 2 O, therefore, the manganese-zirconium-based MOFs confined zero-valent iron nanocomposite prepared by the preparation method of the present invention can effectively encapsulate nano zero-valent iron in the MOF nanopores. This encapsulation strategy can, on the one hand, improve the dispersibility of active sites and inhibit the agglomeration of metal particles (in this embodiment, nano zero-valent iron). On the other hand, the nano-confinement effect can significantly enhance the mass transfer effect during the electrochemical reaction, thereby improving the detection performance of the constructed electrochemical sensor.

[0067] It can be understood that, through the above preparation method, the present embodiment uses Mn-TCPP as a precursor to prepare a 4 The PCN-222(Mn) precursor with a site was then used to convert Fe 2+ The nanocomposite material is immersed in the MOF nanopores and reduced to obtain a nanocomposite material containing manganese zirconium-based MOFs and confined zero-valent iron. In the present invention, the nanocomposite material containing manganese zirconium-based MOFs and confined zero-valent iron can be abbreviated as Fe@PCN-222(Mn) composite material by chemical formula. The prepared nanocomposite material is used to modify the electrode in the electrochemical sensor, and the constructed electrochemical sensor is used to detect trace Hg in water environment. 2+ Based on the nano-confinement effect of Fe@PCN-222(Mn) composite materials, the modified electrode can detect Hg 2+ It can show stronger response signal and catalytic stability.

[0068] Among them, the mechanism of synthesizing MOF by the dual solvent method is to control the crystal growth of MOF by selecting and controlling the solvent. In the dual solvent method, two solvents of different polarities are usually used, one of which is a solvent with a stronger polarity, such as water or ethanol, and the other is a solvent with a weaker polarity, such as n-hexane or toluene. The selection and ratio of these two solvents can change the crystal structure and morphology of MOF. During the synthesis process, metal ions and organic ligands are usually placed in a mixed solvent, and then MOF crystals are formed through a slow volatilization and crystallization process. In the dual solvent method, the strong polar solvent forms hydrogen bonds or coordination bonds with the organic ligands during the crystallization process, thereby controlling the morphology and lattice structure of the MOF crystal. The weak polar solvent can form an ordered structure in the early stage of crystal growth, thereby providing support and control for the crystal growth of MOF. In short, the mechanism of synthesizing MOF by the dual solvent method is to control the morphology and structure of MOF crystals by selecting and controlling the ratio and properties of the solvents, so as to obtain the desired properties and applications.

[0069] The nanocomposite material containing manganese zirconium-based MOFs confined zero-valent iron prepared by the preparation method of this embodiment has MOF nanopores, and the MOF nanopores are used to confine nano zero-valent iron in the MOF nanopores to achieve the fixation of nano zero-valent iron, thereby improving the problems of nano zero-valent iron agglomeration and easy oxidation, thereby improving the electrocatalytic performance of the prepared nanocomposite material containing manganese zirconium-based MOFs confined zero-valent iron. This embodiment can also use the prepared nanocomposite material containing manganese zirconium-based MOFs confined zero-valent iron to contain MOF nanopores, which can significantly promote the high diffusion transfer and reaction of substrates or intermediates during the electrochemical reaction process, thereby improving the detection performance. In addition, the nanocomposite material containing manganese zirconium-based MOFs confined zero-valent iron prepared in this embodiment contains metallic iron and metallic manganese. Through the synergistic catalytic effect of the iron and manganese bimetallic active centers, the electrochemical sensor after the electrode is modified by the nanocomposite material containing manganese zirconium-based MOFs confined zero-valent iron exhibits excellent detection performance and good stability.

[0070] Next, the specific operations of each step in the preparation method of the nanocomposite material containing manganese-zirconium-based MOFs confined zero-valent iron and the specific values ​​of each component are listed.

[0071] A method for preparing a nanocomposite material containing manganese-zirconium-based MOFs confined zero-valent iron, comprising the following steps:

[0072] 1. Preparation of Mn-TCPP, which includes the following steps: adding 100 mL of DMF to a 250 mL round-bottom flask, then adding 0.079 g of TCPP with a concentration of 0.1 mM and 0.253 g of MnCl with a concentration of 1.28 mM to the DMF. 2 ·4H 2O was ultrasonically dissolved, and the mixed solution 1 after ultrasonic dissolution was refluxed at 140°C for 12h, then cooled to room temperature and washed and dried to obtain solid 3. The obtained solid 3 was redispersed in a mixed solution of 30mL THF and 30mL MeOH to obtain a mixed solution 2, and then 100mL of KOH with a concentration of 0.6mol / L was added to the mixed solution 2, and refluxed at 80°C for 12h, and then HCl with a concentration of 1mol / L was added dropwise to the mixed solution 2 after reflux, and solid 4 was precipitated in the mixed solution 2, and HCl was continued to be added until solid 4 was no longer precipitated. The solid 4 in the mixed solution 2 was collected by filtering the mixed solution 2, and the collected solid 4 was washed with deionized water, and then vacuum dried at 60°C for 12h to obtain Mn-TCPP.

[0073] 2. Preparation of PCN-222 (Mn) precursor: 70 mg ZrOCl 2 8H 2 O, 50 mg of Mn-TCPP and 2700 mg of benzoic acid were dissolved in 16 mL of DMF to obtain suspension 4. Suspension 4 was placed in a reactor with a polytetrafluoroethylene liner and reacted at 120°C for 24 hours to obtain suspension 5. The obtained suspension 5 was cooled and filtered to obtain crystals, which were PCN-222 (Mn) crystals. The PCN-222 (Mn) crystals after filtration were collected, and then washed three times with DMF and ethanol respectively, and finally vacuum dried at 120°C for 12 hours to obtain PCN-222 (Mn) precursor.

[0074] 3. Preparation of Fe@PCN-222(Mn) composite material: Weigh 0.2g of PCN-222(Mn) precursor prepared in step 2 and dissolve it in 20mL of deionized water, and perform ultrasonic treatment to disperse it evenly to obtain suspension 1. Heat suspension 1 to 90°C on a stirrer, and add 4mg of Fe(NO 3 ) 2 and 2 mg of p-aminobenzoic acid, and continued stirring for 2 h to obtain suspension 2. Suspension 2 was filtered to obtain solid 1. The purpose of filtering was to remove DMF, and then the obtained solid 1 was dried for 6 h. The dried solid 1 was then transferred to 20 mL of ethylene glycol, and 1 mL of NaBH with a concentration of 4 mg / mL was added dropwise to the ethylene glycol. 4, so that it undergoes a reduction reaction, the reduction reaction time is 30 minutes, and after the reduction reaction is completed, a suspension 3 is obtained. The suspension 3 is centrifuged to obtain a solid 2, and then the obtained solid 2 is washed three times with acetone. The purpose of washing three times is to remove the unreacted substances on the surface. The washed solid 2 is dried in a vacuum drying oven at 60°C for 12 hours to obtain a Fe@PCN-222(Mn) composite material.

[0075] The Fe@PCN-222(Mn) composite material prepared by the above steps is a manganese-containing zirconium-based MOFs nanocomposite material.

[0076] In the actual experimental process, the applicant also prepared two other materials, namely PCN-222 and Fe / PCN-222 (Mn). The specific preparation steps of these two materials are introduced below.

[0077] A method for preparing PCN-222 material comprises the following steps: 70 mg ZrOCl 2 8H 2 O, 50 mg TCPP and 2700 mg benzoic acid were dissolved in 16 mL DMF to obtain suspension VII. Suspension VII was then placed in a reactor with a polytetrafluoroethylene liner and reacted at 120°C for 24 hours to obtain suspension VIII. The obtained suspension VIII was cooled and filtered to obtain crystals, and the crystals obtained at this time were PCN-222 crystals. The obtained PCN-222 crystals were collected, and then the collected PCN-222 crystals were washed three times with DMF and ethanol respectively, and finally the washed PCN-222 crystals were vacuum dried at 120°C for 12 hours to obtain PCN-222.

[0078] A method for preparing Fe / PCN-222(Mn) material, comprising the following steps: weighing the PCN-222(Mn) precursor prepared in step 2, dissolving it in 20 mL of deionized water, and performing ultrasound to disperse it uniformly to obtain suspension 9. The suspension 9 is placed on a stirrer, and then 4 mg of Fe(NO 3 ) 2 , and stirred for 10 min to obtain suspension 10. Then, 1 mL of 4 mg / mL NaBH 4 , and react for 5 minutes to obtain suspension XI. The suspension XI was centrifuged to obtain solid V, which was washed three times with deionized water and then dried in a vacuum drying oven at 60°C for 12 hours to obtain Fe / PCN-222 (Mn) material.

[0079] The prepared PCN-222, PCN-222(Mn), Fe / PCN-222(Mn) and Fe@PCN-222(Mn) were observed under an X-ray diffractometer. Figure 1 XRD pattern of .

[0080] Through Figure 1 The XRD pattern analysis shows that Figure 1 The diffraction peaks at 2θ=4.94°, 7.14°, and 8.34° in the X-ray diffraction spectrum of PCN-222 confirm the successful synthesis of PCN-222. By analyzing the X-ray diffraction spectrum of PCN-222(Mn), it can be seen that its diffraction peaks are basically consistent with those of PCN-222, which proves that the introduction of Mn has no effect on the crystal structure of PCN-222(Mn), and no new diffraction peaks related to Mn are observed, which can indicate that the manganese atoms in PCN-222(Mn) are highly dispersed, and no manganese oxides or metal clusters are formed. It exists in the form of manganese atoms. PCN-222(Mn) is a highly stable MOF material. It uses Mn-TCPP as a precursor and reacts with ZrOCl 2 8H 2 O was synthesized by hydrothermal reaction. The X-ray diffraction patterns of Fe / PCN-222(Mn) and Fe@PCN-222(Mn) were analyzed again, and it was found that the doping of Fe resulted in the appearance of new diffraction peaks at 44.66° and 65.18°, corresponding to the (110) and (200) crystal planes of α-Fe, respectively. This proves that Fe / PCN-222(Mn) and Fe@PCN-222(Mn) were successfully prepared.

[0081] The morphologies of Fe / PCN-222(Mn) and Fe@PCN-222(Mn) were observed by scanning electron microscopy. Figure 2 The morphology of Fe / PCN-222(Mn) and Fe@PCN-222(Mn) was observed by transmission electron microscopy. Figure 3 By analyzing Figure 2 and Figure 3 It can be seen that both Fe / PCN-222(Mn) and Fe@PCN-222(Mn) have obvious nanorod-like structures. The nanorod-like structures are PCN-222(Mn), while in Fe / PCN-222(Mn), nano zero-valent iron (i.e., Fe 0 ) did not aggregate in a large area, but deposited on the surface of PCN-222(Mn). No nano-zero-valent iron (Fe) was observed on the surface of the Fe@PCN-222(Mn) composite. 0) particles are not aggregated, but embedded in the MOF matrix. This proves that the prepared Fe / PCN-222(Mn) and Fe@PCN-222(Mn) can solve the problems of agglomeration and easy oxidation of nano zero-valent iron. Therefore, the reaction activity of nanomaterials in nano zero-valent iron and the reduction characteristics of zero-valent iron can be used, which is beneficial to the adsorption and reduction of heavy metal ions in the electrochemical analysis process, thereby amplifying the electrochemical response signal of the electrochemical sensor, thereby improving the detection sensitivity of the constructed electrochemical sensor. In addition, by Figure 2 and Figure 3 It can also be known that the prepared Fe@PCN-222(Mn) composite material is Fe 0 The Fe@PCN-222(Mn) composite material prepared is confined in the MOF matrix, so the Fe@PCN-222(Mn) composite material prepared has nano-confinement, and the Fe in the prepared Fe / PCN-222(Mn) 0 It is on the surface of PCN-222(Mn).

[0082] Based on the nano-confinement effect, the prepared Fe@PCN-222 (Mn) composite material has the following advantages: (i) it can adjust the charge density distribution of nanomaterials and improve the stability and electrocatalytic activity of the prepared materials; (ii) it can inhibit the agglomeration of nano zero-valent iron particles and improve the dispersion of active sites; (iii) it can significantly enhance the mass transfer effect during the electrochemical reaction.

[0083] In addition, in this embodiment, the structure of the prepared Mn-TCPP is as follows Figure 4 As shown, through Figure 4 It can be seen that the Mn in Mn-TCPP forms coordination with four N atoms to obtain a highly dispersed Mn-N 4 structure.

[0084] Example 2

[0085] A method for constructing an electrochemical sensor using a nanocomposite material containing manganese zirconium-based MOFs confined zero-valent iron, comprising the nanocomposite material containing manganese zirconium-based MOFs confined zero-valent iron prepared in Example 1. The nanocomposite material containing manganese zirconium-based MOFs confined zero-valent iron is used as a modified electrode material to modify an electrode in an electrochemical sensor.

[0086] A method for constructing an electrochemical sensor using a nanocomposite material containing manganese zirconium-based MOFs confined zero-valent iron, comprising modifying an electrode using the nanocomposite material containing manganese zirconium-based MOFs confined zero-valent iron prepared in Example 1, wherein the specific steps of modifying the electrode are: dissolving the prepared nanocomposite material containing manganese zirconium-based MOFs confined zero-valent iron in deionized water and dispersing it evenly by ultrasound to obtain a suspension six; aspirating the suspension six with a micropipette and dripping it into the electrode of the electrochemical sensor to obtain a modified electrode; and placing the modified electrode in the air to dry.

[0087] In this embodiment, before modifying the electrode, the electrode needs to be pretreated. The specific steps of the pretreatment are: polish the electrode with 1.0μm, 0.3μm and 0.05μm aluminum oxide powder respectively until the electrode presents a mirror surface; then, the polished electrode is placed in nitric acid aqueous solution, ethanol aqueous solution and deionized water for ultrasonic treatment respectively. After the ultrasonic treatment, the electrode is dried at room temperature for use.

[0088] The volume ratio of nitric acid to water in the nitric acid aqueous solution is 1:1; the volume ratio of ethanol to water in the ethanol aqueous solution is 1:1.

[0089] Wherein, the electrode can be a glassy carbon electrode.

[0090] The electrochemical sensor constructed by the above construction method can be used to detect trace Hg in water environment. 2+ Conduct testing.

[0091] The following is a specific construction method for constructing an electrochemical sensor using a nanocomposite material containing manganese-zirconium-based MOFs confined zero-valent iron: The glassy carbon electrode is polished with 1.0μm, 0.3μm and 0.05μm alumina powders respectively until the glassy carbon electrode presents a mirror surface. Then, the polished glassy carbon electrode is placed in a nitric acid aqueous solution, an ethanol aqueous solution and deionized water for ultrasonication respectively, and the glassy carbon electrode after ultrasonication is dried at room temperature for later use. The ultrasonication process is specifically to first place the polished glassy carbon electrode in a nitric acid aqueous solution for ultrasonication for 2 minutes, then in an ethanol aqueous solution for ultrasonication for 2 minutes, and finally in deionized water for ultrasonication for 2 minutes.

[0092] 1 mg of the Fe@PCN-222 (Mn) composite material prepared in Example 1 was dissolved in 1 mL of deionized water, and then ultrasonicated for 2 min to make it evenly dispersed. Then 5 μL of the ultrasonicated suspension was taken with a micropipette and dropped on the treated glassy carbon electrode to modify the glassy carbon electrode, and the modified electrode was placed in the air to dry.

[0093] In this embodiment, differential pulse stripping voltammetry can be used to detect Hg 2+ Perform electrochemical detection.

[0094] In the constructed electrochemical sensor for Hg 2+ Before conducting a verification experiment on the detection performance, it is necessary to conduct an optimization experiment to determine the constructed electrochemical sensor for Hg 2+ Experimental conditions for detection. Since the optimization experiment of the electrochemical sensor is a very conventional experiment, it will not be described in detail in this embodiment. The electrochemical sensor constructed in this embodiment 2 was optimized to obtain the Hg 2+ The experimental conditions for the detection were as follows: the buffer solution was 0.1 M NaAc-HAc (pH 5.0), the deposition potential was -1.5 V, and the enrichment time was 180 s. Other parameters for the electrochemical detection were as follows: the transition voltage was 5 mV, the amplitude was 5 mV, the pulse amplitude was 50 mV, the pulse width was 50 ms, the sampling width was 40 ms, and the pulse period was 0.1 s.

[0095] In this embodiment, the applicant also used the prepared PCN-222, PCN-222(Mn), Fe / PCN-222(Mn) and Fe@PCN-222(Mn) to modify the electrodes, respectively, to construct a series of electrochemical sensors, and these constructed electrochemical sensors were tested for 0.7 μM Hg under the experimental conditions obtained by the optimization experiment. 2+ The electrochemical response signal curve is as follows: Figure 5 shown.

[0096] By observation Figure 5 It can be seen that Hg is shown at 0.28V (compared with Ag / AgCl). 2+ The response current signal is 1.34W, and the current intensity on the electrode modified by the Fe@PCN-222(Mn) composite material is the highest. This proves that the prepared Fe@PCN-222(Mn) composite material can enhance the detection sensitivity of the electrochemical sensor.

[0097] Furthermore, in this embodiment, the electrochemical sensor after the Fe / PCN-222 (Mn) modified electrode and the electrochemical sensor after the Fe@PCN-222 (Mn) modified electrode were tested by differential pulse stripping voltammetry for Hg in the concentration range of 0 μmol / L, 0.1 μmol / L, 0.2 μmol / L, 0.3 μmol / L, 0.4 μmol / L, 0.5 μmol / L, 0.6 μmol / L, 0.7 μmol / L, 0.8 μmol / L, 0.9 μmol / L, and 1 μmol / L. 2+ The stripping voltammetry curve is obtained. Figures 6 to 9 .in Figure 6 The electrochemical sensor after Fe / PCN-222(Mn) modified electrode was used to test the above different concentrations of Hg2+ Graph of different voltages and response currents. Figure 7 The electrochemical sensor after Fe / PCN-222(Mn) modified electrode was used to test different concentrations of Hg 2+ The standard curve of Figure 8 In order to test the Hg in the above different concentration ranges through the electrochemical sensor after Fe@PCN-222(Mn) modified electrode 2+ Graph of different voltages and response currents. Fig. 9 The electrochemical sensor of Fe@PCN-222(Mn) modified electrode was used to test different concentrations of Hg 2+ By analyzing Figure 6 and Figure 8 It can be seen that the electrochemical sensor after the Fe / PCN-222(Mn) modified electrode and the electrochemical sensor after the Fe@PCN-222(Mn) modified electrode are sensitive to Hg in the concentration range of 0.1μmol / L to 1μmol / L. 2+ It has a good electrochemical response. Therefore, it is shown that the electrochemical sensor after the Fe / PCN-222 (Mn) modified electrode and the electrochemical sensor after the Fe@PCN-222 (Mn) modified electrode can detect Hg in the concentration range of 0.1 μmol / L to 1 μmol / L. 2+ In addition, the electrochemical sensor after Fe@PCN-222(Mn) modified electrode is better than the electrochemical sensor after Fe / PCN-222(Mn) modified electrode in detecting the same concentration of Hg 2+ During detection, the response signal of the electrochemical sensor modified with Fe@PCN-222(Mn) electrode was much larger than that of the electrochemical sensor modified with Fe / PCN-222(Mn). This indicates that the detection sensitivity of the electrochemical sensor modified with Fe@PCN-222(Mn) electrode was much higher than that of the electrochemical sensor modified with Fe / PCN-222(Mn).

[0098] By comparing the electrochemical sensor constructed after Fe@PCN-222(Mn) modified electrode and the electrochemical sensor constructed after Fe / PCN-222(Mn) modified electrode, it can be seen that the nano-confinement effect of zero-valent iron can enhance the sensitivity of the constructed electrochemical sensor.

[0099] By analyzing Figure 7 and Fig. 9 The standard curves in the figure show that the electrochemical response currents in the two curves are related to Hg 2+ There is an excellent linear relationship between the concentrations of Figure 7The standard curve equation of the standard curve is Y = -0.273 + 13.16X, Figure 7 The linear fitting degree of the standard curve in R 2 =0.997. Fig. 9 The standard curve equation of the standard curve is: Y = -2.64 + 21.25X, Fig. 9 The linear fitting degree of the standard curve in R 2 =0.972. Where Y is the Hg concentration 2+ Response current value, X is Hg 2+ The concentration value, R 2 is the degree of linear fit.

[0100] The above standard curve can be used to calculate Figure 7 The detection limit in was 11.4 nM, Fig. 9 The detection limit was 7.29 nM.

[0101] Through the above series of experiments, it can be seen that the electrochemical sensor constructed by Fe@PCN-222(Mn) modified electrode has good stability and sensitivity, and can detect 0.1μmol / L~1μmol / L Hg 2+ Conduct effective testing.

[0102] In addition, in this embodiment, the enhancement mechanism of the electrochemical signal on the electrode surface is also explored by spectroscopy. Fig.10 XPS total spectrum. Fig.10 Electrochemical sensor constructed by Fe@PCN-222(Mn) modified electrode for Hg adsorption 2+ The XPS spectrum before and after. Fig.10 Analysis shows that Fig.10 (a) is the adsorption of Hg 2+ From the XPS spectrum of Fe@PCN-222(Mn), we can observe that the binding energy peaks of C1s, N 1s, O 1s, Zr 3d, Mn 2p, and Fe 2p are 286.3 eV, 398.4 eV, 530.1 eV, 182.1 eV, 641.2 eV, and 711.5 eV, respectively. In addition, the binding energy at 102 eV is calibrated as the Hg 4f peak, which indicates that Fe@PCN-222(Mn) has a strong affinity for Hg 2+ It has a certain adsorption capacity. Fig.10 (b) to Fig.10 (c) Hg adsorption by Fe@PCN-222(Mn) 2+ High-resolution energy spectra of C and N elements before and after adsorption. There is no obvious change in the C1s and N1s peaks before and after adsorption. 2+ After that, Fe in Fe 2p spectrum 2+ 2p1 / 2 The binding energy peak position moves toward negative energy, which indicates that it has a tendency to lose electrons ( Fig.10 (d)), while Fe 0 The binding energy peak area decreases, which may be attributed to the coverage of surface Hg atoms. Fig.10 In (e), it can be observed that the adsorption of Hg 2+ After that, the Mn-N at 642eV and 653eV 4 The binding energy peak of Fe@PCN-222(Mn) moves to a lower energy, showing a potential electron gain trend. Based on this, it can be concluded that Fe 0 and Mn-N 4 Hg 2+ The main active sites in the adsorption-reduction process.

[0103] The above describes the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments. The above embodiments and descriptions only describe the principles of the present invention. The present invention may be subject to various changes and improvements without departing from the spirit and scope of the present invention. These changes and improvements fall within the scope of the present invention to be protected. The scope of protection claimed by the present invention is defined by the attached claims and their equivalents.

Claims

1. A method for preparing a nanocomposite material containing manganese-zirconium-based MOFs confined zero-valent iron, characterized in that: It includes the following steps: The PCN-222(Mn) precursor was dissolved in DMF and subjected to ultrasound to obtain a suspension 1; The suspension 1 is placed on a stirrer and heated to 90° C., Fe(NO 3 ) 2 and p-aminobenzoic acid are added under continuous stirring, and stirring is continued for a period of time to obtain a suspension 2; The suspension 2 is filtered to obtain a solid 1, and the solid 1 is dried; the dried solid 1 is transferred into ethylene glycol, and NaBH4 is added dropwise into the ethylene glycol to react for a period of time to obtain a suspension 3; The suspension three is centrifuged to obtain a solid two, the collected solid two is washed multiple times with an acetone solution, and the washed solid two is dried to obtain a nanocomposite material containing manganese-zirconium-based MOFs confined zero-valent iron; The prepared composite material containing manganese zirconium-based MOFs confined zero-valent iron nanoparticles contains MOF nanopores, which can confine nano-zero-valent iron in the MOF nanopores; the nanocomposite material containing manganese zirconium-based MOFs confined zero-valent iron is used as an electrode modification material to modify the detection of Hg 2+ Electrodes in electrochemical sensors.

2. The method for preparing a nanocomposite material containing manganese-zirconium-based MOFs confined zero-valent iron as claimed in claim 1, characterized in that: The preparation method of the PCN-222 (Mn) precursor comprises the following steps: Dissolve ZrOCl2·8H2O, Mn-TCPP and benzoic acid in DMF to obtain suspension 4; The suspension 4 is placed in a reaction kettle with a polytetrafluoroethylene liner, and the reaction is continued at 120° C. for 24 hours to obtain a suspension 5; The suspension is cooled and filtered to obtain crystals, which are PCN-222 (Mn) crystals. The PCN-222 (Mn) crystals after filtration are collected, and then the collected PCN-222 (Mn) crystals are washed multiple times with DMF and ethanol respectively, and finally the washed crystals are placed at 120° C. and vacuum dried for a period of time to obtain the PCN-222 (Mn) precursor.

3. The method for preparing a nanocomposite material containing manganese-zirconium-based MOFs confined zero-valent iron as claimed in claim 1, characterized in that: The preparation method of the Mn-TCPP comprises the following steps: TCPP and MnCl2·4H2O were added to DMF respectively, and ultrasonically dissolved to obtain a mixed solution 1, the mixed solution 1 was refluxed at 140°C for 12 hours, and then cooled to room temperature, washed with DMF and ethanol and dried to obtain a solid 3; The fixed three is redispersed in a mixture of THF and MeOH to obtain a mixture of two, and then 0.6 mol / L KOH with a volume of 100 mL is added to the mixture of two, and refluxed at 80° C. for 12 h, and then 1 mol / L HCl is added dropwise to the refluxed mixture of two, and solid four will precipitate in the mixture of two, and 1 mol / L HCl is added continuously until the solid four is no longer precipitated; The solid four in the mixed solution two is collected by filtering the mixed solution two, and the collected solid four is washed with deionized water and vacuum dried to obtain the Mn-TCPP.

4. The method for preparing a nanocomposite material containing manganese-zirconium-based MOFs confined zero-valent iron as claimed in claim 1, characterized in that: The manganese-zirconium-based MOFs-confined zero-valent iron nanocomposite material is prepared by a double solvent method.

5. The method for preparing a nanocomposite material containing manganese-zirconium-based MOFs confined zero-valent iron as claimed in claim 1, characterized in that: The prepared manganese-zirconium-based MOFs-confined zero-valent iron nanocomposite material has MOF nanopores, and the MOF nanopores are used to confine nano-zero-valent iron in the MOF nanopores to fix the nano-zero-valent iron.

6. The method for preparing a nanocomposite material containing manganese-zirconium-based MOFs confined zero-valent iron as claimed in claim 1, characterized in that: The prepared manganese-zirconium-based MOFs-confined zero-valent iron nanocomposite material contains a Mn-N4 structure, and the Mn-N4 structure serves as an active site for redox reactions to improve the catalytic activity of redox reactions.

7. A method for constructing an electrochemical sensor using a nanocomposite material containing manganese-zirconium-based MOFs confined zero-valent iron, characterized in that: It includes a method for preparing a nanocomposite material containing manganese-zirconium-based MOFs-confined zero-valent iron as described in any one of claims 1 to 8 to obtain a nanocomposite material containing manganese-zirconium-based MOFs-confined zero-valent iron, and the nanocomposite material containing manganese-zirconium-based MOFs-confined zero-valent iron is used as a modified electrode material to modify an electrode in an electrochemical sensor.

8. The method for constructing an electrochemical sensor using a nanocomposite material containing manganese-zirconium-based MOFs confined zero-valent iron as claimed in claim 7, characterized in that: The method comprises modifying an electrode by using the prepared nanocomposite material containing manganese zirconium-based MOFs confined zero-valent iron, and the specific steps of modifying the electrode are: The prepared manganese-zirconium-based MOFs-confined zero-valent iron nanocomposite material is dissolved in deionized water and dispersed evenly by ultrasound to obtain a suspension six; the suspension six is ​​aspirated with a micropipette and dropped into the electrode of the electrochemical sensor to obtain a modified electrode; the modified electrode is placed in the air to dry.

9. The method for constructing an electrochemical sensor using a nanocomposite material containing manganese-zirconium-based MOFs confined zero-valent iron as claimed in claim 8, characterized in that: The electrode needs to be pretreated before being modified with the manganese-zirconium-based MOF-confined zero-valent iron nanocomposite material, and the pretreatment steps are: polishing the electrode with 1.0μm, 0.3μm and 0.05μm alumina powders respectively until the electrode presents a mirror surface; then placing the polished electrode in nitric acid aqueous solution, ethanol aqueous solution and deionized water respectively for ultrasonication, and the electrode after ultrasonication is dried at room temperature for use.

10. The method for constructing an electrochemical sensor using a nanocomposite material containing manganese-zirconium-based MOFs confined zero-valent iron as claimed in claim 8, characterized in that: The electrochemical sensor constructed is used to detect trace Hg in water environment 2+ The electrochemical sensor detects Hg 2+ The concentration range is 0.1μmol / L~1μmol / L.

Citation Information

Cited By

  • Heavy metal removal method for constructing micro electric field based on cooperation of metal self-corrosion and ion confinement

    CN120646980A